Erectile Dysfunction among People Who Use Ketamine and Poly-Drugs. Issue 2 (14th March 2016) - Suppiah, Batumalai; Vicknasingam, Balasingam; Singh, Darshan; Narayanan, Suresh
ABSTRACT: Despite the rise in recreational use of ketamine in Malaysia, there have been no studies of users or of the health-related consequences they face. This study was initiated to examine ketamine use and its health consequences. A structured questionnaire was used to elicit information. A final sample of 127 males was divided into persons who used only ketamine and those who were poly-drug users. Each group was further divided into long-period and short-period users. Urine toxicology screening for ketamine and other illicit drugs commonly used in Malaysia was also done. Our findings corroborate those of earlier studies that link ketamine use to urological problems such as frequent urination, dysuria, incontinence, painful bladder, nocturia, and urinary urgency. A new finding in this study is the significant association between ketamine use and erectile dysfunction, such that higher odds of reporting erectile dysfunction were linked to long-period users. Our findings strengthen the case for early intervention, as ketamine users are drawn from young and unmarried male participants. The association of ketamine use with erectile dysfunction, if substantiated, will help physicians in their diagnosis of erectile dysfunction, particularly among youths.